Improving The Skills Of Mothers In Rural Areas In Accelerating The Development Of Motor Skills In Early Childhood - Eldrian, Febianne; Gusmira, Yuni Handayani; Ma’arif, Mashdarul; Lestari, Dhina Lydia; Amellia, Ade Yuli (Universitas Pahlawan Tuanku Tambusai, 2024)
For five days the author/servant carried out adpatas, took care of administration in the village, and made introductions to local residents until the author decided to provide education on how to accelerate children's motoric growth in rural areas for every mother and prospective mother in Batu Kembang village. The result in this article show 1. The writer/servant discovered this problem because he read literature related to health and then related it to fellow servants and the surrounding community and it turns out the problem is suitable because there are still many mothers and prospective mothers in Batu Kambing village who don't know how to accelerate motor development in early childhood. . 2). This service is carried out for one month with a general description of activities, namely adaptation, completing administrative matters, and discussions with the local community in the first week. Conduct theoretical education in the second week. Practice gross motor and fine motor skills in the third and fourth weeks. 3). Education theoretically includes 4 materials, namely understanding motor skills, the function of motor development in early childhood, how to accelerate motor development in early childhood, and how to overcome hampered motor development at an early age. 4). Gross motor practices include running around, gobak sodor, throwing a ball, and children being involved in household work. Fine motor practice includes playing with crayons, cutting, and putting together puzzles.